2019
DOI: 10.1039/c9tc04079j
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal control of liquid crystalline mesophases from surfactants with photoswitchable tails

Abstract: Azobenzene surfactants transform into a rich variety of single-component liquid crystalline mesophases through strategic control of molecular design, concentration, temperature and light, paving the way to new photoresponsive materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 44 publications
1
29
0
Order By: Relevance
“…6.1.1. Multimodal control of liquid crystalline mesophases from surfactants with photoswitchable tails (Houston et al, 2019). Lytrophic liquid crystalline phases (LLC), derived from concentration-dependant self-assembly of surfactants, are being developed for a variety of applications including drug-delivery vessels, optical modulators or templates for the construction of porous materials.…”
Section: Mail-inmentioning
confidence: 99%
See 1 more Smart Citation
“…6.1.1. Multimodal control of liquid crystalline mesophases from surfactants with photoswitchable tails (Houston et al, 2019). Lytrophic liquid crystalline phases (LLC), derived from concentration-dependant self-assembly of surfactants, are being developed for a variety of applications including drug-delivery vessels, optical modulators or templates for the construction of porous materials.…”
Section: Mail-inmentioning
confidence: 99%
“…Azobenzene undergoes trans-cis photoisomerization under UV irradiation, allowing it to act as a prototypical molecular switch. Houston et al (2019) used the B21 MPS cell to obtain SAXS data that showed the ability of azobenzene photosurfactants (AzoPS) to form LLC phases. The SAXS data allowed direct assignment of the phase symmetry of the surfactants, with the most common being hexagonal-phase and lamellar-phase symmetry, depending upon the alkyl tail groups and polar head groups of the AzoPS's, in both the cis and trans forms [ Fig.…”
Section: Mail-inmentioning
confidence: 99%
“…Azobenzene-based materials have been applied to liquidcrystalline (LC) materials as thermotropic, 102-106 lyotropic [107][108][109][110] and polymeric systems [111][112][113][114][115][116][117][118] for a diverse array of applications. Some recent reviews of various applications of azobenzene containing liquid crystals can be found here.…”
Section: Liquid Crystals (Lcs)mentioning
confidence: 99%
“…24,25 In tandem with these advances, there have been several studies on the selfassembly behaviour of AzoTABs at low concentration, 4a,b,26,27 but as yet no reports of their high-concentration behaviour. While the formation of lyotropic liquid crystal (LLC) phases has been described for neutral AzoPS, [28][29][30][31] no such accounts exist for AzoTABs. AzoTABs generally have fewer hydrogen bonding sites than their neutral counterparts, which is expected to hinder their LLC phase-forming ability.…”
mentioning
confidence: 99%
“…S2, ESI †), similar to values obtained for neutral AzoPS. 30 High concentration solutions of C 8 AzoOC 2 TAB (10-40 wt% in water) were analysed using polarised optical microscopy (POM), small-angle X-ray scattering (SAXS) and differential scanning calorimetry (DSC) to determine the phase behaviour in this concentration regime. Fig.…”
mentioning
confidence: 99%